Intercommunal Relations in the M'Zab During the Pre-Colonial Period: Between Collaboration and Conflict - Mohammedi, Louiza; Nora, Gueliane (Future Science, 2024)
This article explores intercommunity relations in the M'Zab region of southern Algeria during the pre-colonial period. Known as a refuge for the Mozabites, Berber ibadites, the region boasted a unique identity with its own institutions and a history of autonomy. The Mozabites coexisted with Jews, ḥamriyas, and various nomadic and semi-nomadic tribes, who were mainly Malikite and Arabic-speaking. Their interactions ranged from economic cooperation to conflict, influenced by circumstances and alliances. The study aims to clarify how the Mozabites engaged with foreigners and lived alongside them before French colonization in 1882. Relying on documentary research into demographic composition, historical roles of different groups, and existing power dynamics, along with local interviews, the paper sheds light on these complex relationships. Understanding these historical interactions is crucial for grasping the current ethnic and doctrinal conflicts in the region, including those in 2015, and highlights the im-portance of historical context in contemporary community relations.